Protección del consumidor en los mercados: una perspectiva romanística del derecho de información y la transactio - Zamora Manzano, José Luis (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In the present paper, we will focus on information on consumer protection and mediation which allows a much quicker resolution of any conflicts that arise in the matter of consumption, emphasizing the sources of Roman law where we find the Consumer protection carried out by the aediles, who were in charge of controlling and monitoring the markets, speculation and weights and measures, for this we analyze mainly sources such as D.21.1.1.1 and the vice that originated the redhibition D.21.16 and 21.1.14.10, among others. Moreover, the jurisdiction of the aediles developed in the same way as the praetors within their sphere of competence of the markets, the resolution of conflicts through the transaction that implies a history of mediation and that today is articulated as an alternative method of dispute resolution. Subsequently we analyze the bases that remain on some principles of current consumer law and the panorama that shows the incorporation of EU directives such as 2011/83/EU and the recent 2013/11/EU that encourages alternative dispute resolution (ADR).